1992
DOI: 10.5935/0305-7518.19920028
|View full text |Cite
|
Sign up to set email alerts
|

The allocation of leprosy patients into paucibacillary and multibacillary groups for multidrug therapy, taking into account the number of body areas affected by skin, or skin and nerve lesions

Abstract: In Nepal, the setting up and maintaining of reliable services for slit skin smears has proven difficult. A clinical classification system for leprosy has therefore been developed to assist in the allocation of patients to either paucibacillary or multibacillary groups for the purposes ofmulhple drug therapy (MDT), using 9 body areas: head (I), arms (2), legs (2), trunk (4). Patients with more than two areas of the body affected are grouped as multibilcillary (MB) and those with only one or two areas affected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
1
16
1
2
Order By: Relevance
“…[6] , study in Nepal by van Brakel showed nearly 8.7%. [7] and Sarkar et all showed 9.4% but in our study compared to all other studies slightly higher 13% of pure neuritic leprosy going for deformity. Males suffered more than their female counterparts, which may be due to their more exposure to outdoor activities making them more vulnerable to different injuries.…”
Section: Discussioncontrasting
confidence: 65%
“…[6] , study in Nepal by van Brakel showed nearly 8.7%. [7] and Sarkar et all showed 9.4% but in our study compared to all other studies slightly higher 13% of pure neuritic leprosy going for deformity. Males suffered more than their female counterparts, which may be due to their more exposure to outdoor activities making them more vulnerable to different injuries.…”
Section: Discussioncontrasting
confidence: 65%
“…A study in South India by Mahajan and others had found lower proportion of neuritic leprosy (4.6%) compared to this study [14] but the study in Nepal by van Brakel showed nearly similar proportion (8.7%) of neuritic leprosy patients. [15] Kumar et al, [16] also found (2004) paralytic deformity was highest (26%) among neuritic leprosy patients.…”
Section: Discussionmentioning
confidence: 90%
“…Oskam [8] reviewed previous studies [9][10][11][12][13][14], mostly prior to 1993, that compared the number of skin lesions (although not always with 15 as the cutoff) and body zones involved with skin smears or biopsies with a BI value 10-1 (table 4). The first 3 studies resulted in a low specificity (39%-42%) for a clinical diagnosis of MB leprosy in locations where MB leprosy is more common [9][10][11] but not in areas where it is less common (81%-88%) [12,13]. Misclassifying patients with PB leprosy as having MB leprosy may result in overtreatment, whereas misclassifying patients with MB leprosy as having PB leprosy may result in undertreatment.…”
Section: Methods For the Classification Of Leprosy For Treatment Purpmentioning
confidence: 99%